Improving the Quality of Life of Patients with an Underactive Thyroid Through mHealth: A Patient-Centered Approach - Vedrana H?gqvist Tabor; Mikael H?gqvist Tabor; Sarai Keestra; Jean-Etienne Parrot; Alexandra Alvergne (Mary Ann Liebert, 2021)
Background: Three hundred fifty million people worldwide suffer from underactive thyroid conditions, which can lead to infertility, obesity, heart disease, and impaired mental health when poorly managed. Although mobile health (mHealth) applications can be a useful solution for self-managing one's condition, the impact of digital solutions for improving the health of thyroid patients remains unknown. Methods: We used a mixed methods analysis to assess the ways in which a digital approach might benefit thyroid patients. A cross-sectional study was conducted among users of BOOST Thyroid, an mHealth application for patients with an underactive thyroid. We collected data using a modified Short Form 36 Health Survey Questionnaire to measure the impact of in the app on participants' perceived health and quality of life. Participants were asked to (1) score their quality of life before and after using the app, and (2) describe whether and how using the app helped them. Results: We enrolled 406 users (380 females and 26 males), aged 18?78 years. Most participants (95.8%) reported using the app was helpful; of which 68% reported it improved their quality of life and 70.8% reported it had a positive impact on their health. Participants who found the app useful experienced less symptoms and a lower intensity of remaining symptoms. A key factor reported by these participants as helping with managing their health is the information provided in the app. Conclusions: The results support the idea that a patient-centered treatment would benefit from including mHealth tools for a daily self-management of underactive thyroid condition, as it can increase health literacy and improve both one's health status and quality of life.